Application of two types of suspensory fixation in reconstruction of anterior cruciate ligament with a semitendinosus-gracilis graft – A randomized prospective study - Djordjević, Dušan; Petrović, Milan; Djordjević Žunčić, Snežana; Stojiljković, Predrag; Golubović, Ivan; Kadija, Marko; Micić, Ivan (Vojnosanitetski pregled, 2021)
Background/Aim. Injury to the anterior cruciate ligament (ACL) of the knee is the most common ligament injury that requires operative treatment. So far, multiple ACL reconstruction (ACLR) techniques using a variety of graft types and implants that fixate the grafts have been described. The aim of the study was to compare two different ACLR techniques using two implant types for suspensory graft fixation in the femoral tunnel. Methods. This randomized-prospective study encompassed 60 patients/subjects who underwent ACLR in the period between January 2015 and December 2017 at the Department of Orthopaedics and Traumatology of Military Hospital “Dr Vladan Djordjević” Niš. The ACLR in all patients included in the study was performed using a quadruple semitendinosus-gracilis (STG) graft with two types of suspensory fixation on the lateral femoral cortex, whereas the graft fixation in the tibial tunnel was performed using an osteoconductive bioresorbable screw. The post-operative knee stability was assessed 24 months after surgery using the Lachman test and the lateral pivot shift test, as well as the KT-1000 arthrometer test. Results. In patients whose graft was fixated using a fixed-length loop implant, the mean post-surgery knee stability, measured with the KT-1000, was 1.167 ± 0.780; in patients whose graft was fixated using an adjustable-length loop implant, the mean value of the KT-1000 was 1.100 ± 0.894 (p = 0.605). The mean post-surgery International Knee Documentation Committee (IKDC) score for the fixed-length loop group was 84.887 ± 9.0207, while for the adjustable-length loop the score was 88.327 ± 7.302. The mean Lysholm score was 93.50 ± 6.872 for the fixed-length loop group of patients and 94.00 ± 5.527 for the adjustable-length loop group of patients. Conclusion. Both types of implants can be used with success during ACLR, because the functional results of operative treatment using both implants were identical after surgery. Background/Aim. Injury to the anterior cruciate ligament (ACL) of the knee is the most common ligament injury that requires operative treatment. So far, multiple ACL reconstruction (ACLR) techniques using a variety of graft types and implants that fixate the grafts have been described. The aim of the study was to compare two different ACLR techniques using two implant types for suspensory graft fixation in the femoral tunnel. Methods. This randomized-prospective study encompassed 60 patients/subjects who underwent ACLR in the period between January 2015 and December 2017 at the Department of Orthopaedics and Traumatology of Military Hospital “Dr Vladan Djordjević” Niš. The ACLR in all patients included in the study was performed using a quadruple semitendinosus-gracilis (STG) graft with two types of suspensory fixation on the lateral femoral cortex, whereas the graft fixation in the tibial tunnel was performed using an osteoconductive bioresorbable screw. The post-operative knee stability was assessed 24 months after surgery using the Lachman test and the lateral pivot shift test, as well as the KT-1000 arthrometer test. Results. In patients whose graft was fixated using a fixed-length loop implant, the mean post-surgery knee stability, measured with the KT-1000, was 1.167 ± 0.780; in patients whose graft was fixated using an adjustable-length loop implant, the mean value of the KT-1000 was 1.100 ± 0.894 (p = 0.605). The mean post-surgery International Knee Documentation Committee (IKDC) score for the fixed-length loop group was 84.887 ± 9.0207, while for the adjustable-length loop the score was 88.327 ± 7.302. The mean Lysholm score was 93.50 ± 6.872 for the fixed-length loop group of patients and 94.00 ± 5.527 for the adjustable-length loop group of patients. Conclusion. Both types of implants can be used with success during ACLR, because the functional results of operative treatment using both implants were identical after surgery.